The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.30924/mjcmi/2017.22.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Star marketer’s impact on the market strategy choice

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In spite of large body of work on how to drive organizational ambidexterity, established incumbent organizations tend to be exploitative in nature (see Lavie et al, 2010). Organizational preference for exploitation versus exploration can arise from individual characteristics of key decision‐makers (see Gibson & Birkinshaw, 2004; Laureiro‐Martínez et al, 2015; Vlasic et al, 2017; Yadav et al, 2007) with exploitation and exploration being “separate behaviors involving different mind processes” (Cristofaro et al, 2022a). Therefore, to understand the organizational preference for exploration versus exploitation, it is important to understand which cognitive profiles tend to get promoted to the top strategic positions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In spite of large body of work on how to drive organizational ambidexterity, established incumbent organizations tend to be exploitative in nature (see Lavie et al, 2010). Organizational preference for exploitation versus exploration can arise from individual characteristics of key decision‐makers (see Gibson & Birkinshaw, 2004; Laureiro‐Martínez et al, 2015; Vlasic et al, 2017; Yadav et al, 2007) with exploitation and exploration being “separate behaviors involving different mind processes” (Cristofaro et al, 2022a). Therefore, to understand the organizational preference for exploration versus exploitation, it is important to understand which cognitive profiles tend to get promoted to the top strategic positions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The literature distinguishes between management accounting and strategic management accounting. The main differences between both are presented in However, in a highly competitive environment, companies are more likely to focus on future events (Vlašić et al, 2017).…”
Section: R -Realisticmentioning
confidence: 99%
“…In consumer decision-making literature, Wright’s (1974) foundational research showed that, under time pressure, consumers tend to emphasize negative traits of a product. Since then, other research in various shopping contexts suggests that manipulations of time pressure, such as via scarcity of products (Devlin et al, 2007; Soliman, 2017) or length of sale (Aggarwal & Vaidyanathan, 2003), can dictate the strategy with which consumers approach purchases (Chowdhury et al, 2009; Vlašić et al, 2011) and their acceptance of risk (Shehryar, 2008). Indeed, time pressure has been shown to impact the ability of consumers to investigate product information (Kardes et al, 2006; do Prado & Lopes, 2016) and reduces the amount of time they spend browsing unfamiliar products (Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%